A Supply-Lock Competitive Market for Investable Products - Wang, Yong-Bo; Lu, Jin-Ray (Asian Development Policy Review, 2016)
We propose a new market structure, a supply-lock competition (SLC), for analyzing transactions of investable goods. This study explains and analyzes how the SLC is applicable for transactions of stock, art, real estate, currency, and scarce goods. We suggest that the formation and fluctuation of the market price for these investable assets are not only related to their intrinsic values or investors’ behavior, but are also derived from supply restriction. A mechanism of the SLC market structure benefits market efficiency but also continues volatility of asset prices in secondary markets as well. We demonstrate that a demand orientation dominates the valuation of investable assets, resulting in a divergence of market price and intrinsic value.